Costly Efficiencies: Health Care Spending, COVID-19, and the Public/Private Health Care Debate - Christopher Mouré (Review of Capital as Power, 2022)
* Winner of the 2022 RECASP First Essay Prize * Proponents of private healthcare often claim that the private sector is more `efficient' at delivering healthcare services. This paper tests the privatization thesis in the context of the COVID-19 pandemic. Using a large sample of countries, I investigate how healthcare privatization affects the correlation between COVID-19 death rates and healthcare spending (as a share of GDP). In countries with healthcare that is mostly public, I find no correlation. However, in countries with significant healthcare privatization, I find that greater healthcare spending was associated with more COVID-19 deaths. This result is consistent with the theory of `capital as power', which argues that to earn profits, the private sector seeks to strategically limit the provision of social goods.
Keywords: P16; I1; 330; capital as power; COVID-19; health; profit; sabotage